190 Winter vs. year-round supplementation of mature beef cows on feedlot performance and carcass characteristics of steer progeny. (28th November 2020) - Palmer, Elizabeth; Vedovatto, Marcelo; Ranches, Juliana; Gouvea, Vinicius; Oliveira, Rhaiza; Poore, Matt H; Arthington, John; Vendramini, Joao; Moriel, Philipe
Abstract: This study evaluated the effects of year-round supplementation of molasses/urea or wheat middlings-based range cubes to mature cows on subsequent feedlot growth, immunity, and carcass characteristics of their steer progeny. On d 0, 82 mature Brangus cows were stratified by BW and BCS (433 ± 47 kg; 4.6 ± 0.77) and randomly allocated into 1 of 6 bahiagrass pastures (13–14 cows/pasture). Treatments were randomly assigned to 2 pastures/treatment and consisted of supplementation with molasses/urea during winter (MOL-W), or year-round supplementation with molasses/urea (MOL-Y) or range cubes (CUB-Y). Supplements were isocaloric and isonitrogenous (75% TDN, 20% CP; DM basis) and offered at a total yearly supplement DM amount of 272 kg/cow. On d 423, all calves were weaned, and 33 steers were randomly selected for the feedlot phase. Steers were penned based on cow prepartum pasture distribution and managed similarly until slaughter (d 661). Data were analyzed as complete randomized design using MIXED procedure of SAS, pasture as the experimental unit, treatment as fixed effect, and pasture(treatment) and steer(pasture) as random effects. Dry matter intake did not differ (P ≥ 0.70), but MOL-Y and MOL-W steers had greater (P = 0.05) overall ADG vs. CUB-Y steers. Plasma haptoglobin concentrations tended (P = 0.06) to be greater for CUB-Y vs. MOL-W, and intermediate for MOL-Y. Serum titers against bovine viral diarrhea virus-1 and parainfluenza-3, hot carcass weight, REA, and YG did not differ (P ≥ 0.16) among treatments, but back fat thickness was greater (P = 0.03) for MOL-W vs. MOL-Y and CUB-Y. The percentage of carcasses grading Choice did not differ (P = 0.35) among treatments, but more carcasses tended (P = 0.08) to grade low Choice for MOL-W vs. CUB-Y and MOL-Y. Therefore, providing molasses/urea supplementation to mature beef cows during winter only or year-round increased steer post-weaning feedlot performance and carcass quality compared to steers born from cows offered year-round supplementation with range cubes.